Can health benefit outcomes benefit public health budget professionals. Issue 1 (5th March 2018) - Candreva, Phillip; Eger, Robert
Abstract : Purpose: To assist in achieving cost effective health care allocations in a collective choice setting, the purpose of this paper is to illustrate the use of a tool not common in the public budgeting literature but is common in the health economics literature. Design/methodology/approach: Through a meta-analysis of the health care spending literature that computed the value of quality-adjusted life years, the authors provide an alternative approach for budgeters and policymakers. Findings: The authors provide an alternative approach for budgeters and policymakers for weighing the benefits of alternative health care spending allocations. Originality/value: The authors introduce an alternative approach for weighing the benefits of alternative health care spending allocations. As a tool for budgeting professionals, cost per QALY allows for the opportunity to raise cost-effectiveness of public health expenditures as a tool for governments to allocate resources based on outcomes, rather than inputs.